Digital Finance: A Literature Study - Tihar, Ari (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The financial sector has experienced continuous development in service provision as a result of the digitalization process. This evolutionary process is characterized by increased connectivity and accelerated information processing, both in customer interfaces and in back-office processes. The role of contracts in the current economic context has received significant attention, considering that contracts are a key element of market economic activity. The relevance of digital finance and financial inclusion in efforts to reduce poverty and support economic growth is attracting increasing attention from policy makers and academics. This is due to a number of issues that, if properly addressed, can increase the effectiveness of digital finance for individuals, businesses, governments and the economy as a whole. Digital finance and financial inclusion have several significant benefits for financial service users, digital financial providers, governments and the economy. Wider financial access among poor individuals, lower financial intermediation costs for banks and fintech providers, and higher aggregate spending for governments are some examples of such benefits. The aim of this research is to determine the factors that influence digital finance. This research used a systematic literature review method and collected 15 articles from the Scopus and ScienceDirect pages. The research results show that digital finance is influenced by several variables, both those that influence and those that are influenced. However, no digital finance was found as a moderating variable in this research.